Efforts to Increase Student Learning Activity in Materials Strengthen National Commitment in Online Learning Through Quizizz Educational Game Media in the New Normal Era - Arif Purwanto (http://jagadalimussirry.com/, 2022)
This study aims to determine the process and results of increasing student learning activity in online learning in the new normal era on the material to strengthen national commitment through the Quizizz Educational Game Media. Methods of data collection in the form of observation, questionnaires, and tests. Observations and questionnaires were used to determine the increase in student learning activities in learning and evaluation tests were used to determine student achievement in the material to strengthen national commitment. Based on the results of observations, student learning activities and achievements have increased significantly. Based on student response questionnaires on the use of educational game media quizizz in learning shows that students' responses in learning increase. Thus, overall, the application of quizizz educational game learning media can increase student activity and learning outcomes in Civics learning on materials to strengthen national commitment in this new normal era. For this reason, it is recommended, especially for PPkn’s teachers, the results of this study should be used as information and references in the development of education so that they become creative and innovative learning alternatives